In silico analyses and experimental validation of the MHC class-I restricted epitopes of Ebolavirus GP. (22nd February 2022) - Liu, Yang; Sun, Baozeng; Wang, Jiawei; Sun, Hao; Lu, Zhenhua; Chen, Longyu; Lan, Mingfu; Xu, Jiahao; Pan, Jingyu; Shi, Jingqi; Sun, Yuanjie; Zhang, Xiyang; et al.
Abstract: Ebolavirus (EBOV) causes an extremely high mortality and prevalence disease called Ebola virus disease (EVD). There is only one glycoprotein (GP) on the virus particle surface, which mediates entry into the host cell. Major histocompatibility complex (MHC) class-I restricted cluster of differentiation 8 (CD8 + ) T cell responses are important antiviral immune responses. Therefore, it is of great importance to understand EBOV GP-specific MHC class-I restricted epitopes within immunogenicity. In this study, computational approaches were employed to predict the dominant MHC class-I molecule epitopes of EBOV GP for mouse H2 and major alleles of human leukocyte antigen (HLA) class-I supertypes. Our results yielded 42 dominant epitopes in H2 haplotypes and 301 dominant epitopes in HLA class-I haplotypes. After validation by enzyme-linked immunospot (ELISpot) assay, in-depth analyses to ascertain their nature of conservation, immunogenicity, and docking with the corresponding MHC class-I molecules were undertaken. Our study predicted MHC class-I restricted epitopes that may aid the advancement of anti-EBOV immune responses. An integrated strategy of epitope prediction, validation and comparative analyses was postulated, which is promising for epitope-based immunotherapy development and application to viral epidemics. Abstract : Predicting MHC I-restricted epitopes in Ebolavirus Graphical Abstract: